1986
DOI: 10.2307/1966906
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality in Addis Ababa, Ethiopia

Abstract: Between July and September 1983, a two-stage probability survey was conducted in Addis Ababa, Ethiopia to obtain data on pregnancy outcomes for all women aged 13-49 in 32,215 houses. The survey covered a two-year period, from 11 September 1981 to 10 September 1983. Of the 9,315 women who were pregnant during those two years, 45 died from complications of pregnancy, delivery, and the puerperium. The maternal mortality rate for 1982-83 was estimated to be 566 per 100,000 live births. Mortality was highest for nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 0 publications
2
42
1
Order By: Relevance
“…Indeed, such data from large, well-conducted, population-based studies anywhere in sub-Saharan Africa are sparse. Data from a large household survey in the capital of Ethiopia in 1981-3, of 9315 pregnant women, found an MMR of 566 per 100 000, 7 and this is likely to be lower than that in rural areas. A smaller study, of 5832 households, in another major urban area in south-west Ethiopia found an MMR of 402 per 100 000.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, such data from large, well-conducted, population-based studies anywhere in sub-Saharan Africa are sparse. Data from a large household survey in the capital of Ethiopia in 1981-3, of 9315 pregnant women, found an MMR of 566 per 100 000, 7 and this is likely to be lower than that in rural areas. A smaller study, of 5832 households, in another major urban area in south-west Ethiopia found an MMR of 402 per 100 000.…”
Section: Discussionmentioning
confidence: 92%
“…Female mortality associated with child-bearing in Sweden was 7.4 deaths per 100,000 live births (Kwast, Rochat, & Kidane-Mariam, 1986) from 1980 to 1988. In contrast, maternal death in Ethiopia in 1983 was 566 deaths per 100,000 live births (Kwast et al, 1986). A direct comparison of mortality rates between pregnant and non-pregnant women in rural Malawi, found that pregnancy increased female mortality by 29 per 100,000 women (McDermott et al, 1996).…”
Section: The Risk Of Sexmentioning
confidence: 99%
“…Main contributing factors for this high death includes unsafe abortion, among others [5]. Several studies in Ethiopia indicated that unsafe abortion may account for up to 25-35% of the maternal deaths [6][7][8]. A recent nationwide study on abortion related complications has shown that an estimated number of 17 patients are seen in hospitals for post abortion complications in a month and complications due to abortion were also reported from low-level facilities, which do not provide post abortion care services [9].…”
Section: Introductionmentioning
confidence: 99%